Temporal Fine Structure and Working Memory Abilities on Deciding the Probable Compression Speed in Hearing Aids - Vishal Kooknoor; Jesteena Joy; Hemanth Narayana Shetty (Auditory and Vestibular Research)
Background and Aim: Temporal Fine Structure (TFS) sensitivity and Working Memory (WM) abilities have been widely studied individually as the contributing factors for deciding compression speed in hearing aids. The study aimed to develop a clinical framework for setting optimal compression speed using combination of TFS sensitivity and WM abilities. Methods: Participants were 25 native Kannada-speaking adults (mean age 70 years). We evaluated the participant’s TFS sensitivity using the TFS -Adaptive Frequency (AF) and WM abilities using reading span test. Further, aided sentence recognition in noise was tested to obtain find the signal-to-noise ratio 50% (SNR 50) correct identification happens in Fast Acting Compression (FAC) and Slow Acting Compression (SAC) modes. Results: Individuals with good TFS sensitivity demonstrated significantly lower SNR 50 scores with FAC and individuals with poor WM showed significantly lower SNR 50 with SAC. However, individuals with poor TFS sensitivity and individuals with good WM ability showed no significance on SNR 50 obtained between FAC and SAC. A strong negative correlation existed between TFS sensitivity and SNR 50 in both SAC and FAC modes even after accounting for WM abilities. There was a mild negative correlation between WM abilities and SNR 50 in FAC mode only, but this was not significant after accounting for TFS sensitivity. Conclusion: Using the results of the present study along with the literature findings, a clinical framework was devised to enable the selection of appropriate compression speed for optimal speech understanding with hearing aids.